Momos on two amphorae by the Paris Painter (Limes: Revista de Estudios Clásicos, 2023)
The Etruscan neck amphorae New York 55.7 and Munich 837 (c. 540 BC), both by the Paris Painter, display two subsequent episodes. The first shows, on side B, Turms (Hermes) with Chiron and another messenger walking in a queue so that Turms collect the goddesses and take them to Mount Ida so that Elcsuntre (Paris) solves the dispute. The amphora of Munich shows, on side B, the same anonymous messenger on the amphora of New York leads the procession of gods. He is followed by Turms, who turns around either to give instructions or to introduce the goddesses. The identity of the second messenger has been widely discussed and disputed among scholars of ancient art. My proposal in this paper is that this messenger is Momos, the brother of Eris and god of mockery, and not Satre (Chronus) or Tinia (Zeus) or Priumne (Priam) or Tecrs (Teucer), as has been asserted by other researchers before.
Keywords: vases, Etruscan art, Judgement of Paris, Trojan War